Comportamento da sífilis congênita no Estado do Maranhão - Brasil: análise de 10 anos - MOURA, Maria Madalena Reis Pinheiro (2020)
Congenital Syphilis (SC) is a systemic infectious disease of chronic evolution caused by the bacterium Treponema pallidum, which affects the fetus through the placenta at any gestational period or clinical stage of the disease in untreated or inadequately treated women. The probability of infection of the fetus depends on the stage of maternal syphilis and the time of exposure of the embryo or fetus to the spirochete that causes syphilis. The present study aims to analyze the epidemiological profile of notified cases of congenital syphilis in the state of Maranhão from January 2010 to December 2019. This is an epidemiological, descriptive, retrospective study, with a quantitative approach, with secondary data referring to cases of congenital syphilis reported in the state of Maranhão originating from the Information System on Notifiable Diseases - SINAN and Information System on Live Births - SINASC of the State Health Secretariat. The data revealed increasing coefficients of incidence of congenital syphilis reaching 7.24 per thousand live births (LB) in 2018 and an average incidence coefficient of 3.38 per thousand LB, with Timon being the health region with the highest incidence coefficient with 16.42 per thousand LB. The mothers of the children listed in the study were aged between 20 and 39 years (73.7%), where only 4.1% underwent adequate treatment during the study period and 16.4% of the partners were treated concurrently. With regard to children, 49.5% were notified at birth (0 day), 45.6% did not undergo a treponemic test after 18 months and 75.7% did not perform a CSF test, 92.2% had recent congenital syphilis , with 89.00% surviving and 1.6% dying from congenital syphilis. SC in Maranhão remains a serious public health problem, with incidence remaining above the accepted limit for reaching its elimination. It is well known that efforts in the national purpose of eradicating SC need to be more valued, aiming at an incidence less than or equal to 0.5 cases / 1000 live births. However, an unfavorable situation was observed, demonstrating the importance of knowing the profile of the affected population for the provision of quality prenatal care and uniformity of SC surveillance conducts.